2011
DOI: 10.1016/j.virol.2011.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Identification and pathogenicity of a natural reassortant between a very virulent serotype 1 infectious bursal disease virus (IBDV) and a serotype 2 IBDV

Abstract: Infectious bursal disease virus (IBDV) causes an economically important, immunosuppressive disease in chickens. There are two serotypes of the virus that contain a bi-segmented double-stranded RNA genome. In December 2008, the first very virulent (vv)IBDV was identified in California, USA and in 2009 we isolated reassortant viruses in two different locations. Genome segment A of these reassortants was typical of vvIBDV serotype 1 but genome segment B was most similar to IBDV serotype 2. The CA-K785 reassortant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 43 publications
6
43
0
6
Order By: Relevance
“…This observation is consistent with the phylogeny-based hypothesis that both genome segments may be involved in the emergence of vvIBDV (38,39). Recently, this hypothesis was substantiated by the isolation of three naturally occurring segment B-reassorted vvIBDV isolates, all with reduced pathogenicity in chickens (40,41). Another recent experimental study based on reverse genetics demonstrated that several domains of the IBDV polymerase may contribute to virulence (42).…”
Section: Nfectious Bursal Disease Virus (Ibdv) Of Chickens (Gallus supporting
confidence: 84%
“…This observation is consistent with the phylogeny-based hypothesis that both genome segments may be involved in the emergence of vvIBDV (38,39). Recently, this hypothesis was substantiated by the isolation of three naturally occurring segment B-reassorted vvIBDV isolates, all with reduced pathogenicity in chickens (40,41). Another recent experimental study based on reverse genetics demonstrated that several domains of the IBDV polymerase may contribute to virulence (42).…”
Section: Nfectious Bursal Disease Virus (Ibdv) Of Chickens (Gallus supporting
confidence: 84%
“…16 These primers amplify a 778-bp region of the serotype 2 VP2 gene from nucleotides 686-1,463 and do not amplify genome segment A of serotype 1 IBDV. The amplified serotype 2 segment A product was detected using probe f FAM-5'-GTCGCAA CTCATCCCAAGT-3'.…”
Section: Real-time Rt-pcr Amplificationmentioning
confidence: 99%
“…16 The amplified segment B product was detected using probe f FAM-5'-TACTCAAGCAGATGAT-3'. The cDNA synthesis, pre-denaturation, and PCR conditions were as described previously.…”
Section: Real-time Rt-pcr Amplificationmentioning
confidence: 99%
“…Glutamic acid is characterized by negatively charged (acidic) R group, whereas, the R group in alanine is non polar (hydrophobic). It is probable that this change from negative charge to non-polar may modify the protein folding or the interaction with other molecules that may change the topography of the neutralizing epitopes that may lead to vaccination failure (Jackwood et al, 2011).…”
Section: Discussionmentioning
confidence: 99%